2020
DOI: 10.3390/ijerph17186756
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Consumer Involvement in Mental Health Nursing Education: An Integrative Review

Abstract: This integrative review analyzed the research on consumer involvement in mental health nursing education in the last decade. We aimed to derive the main contents, methods, and outcomes of education using consumer involvement for mental health nursing students. We searched six electronic databases using English and Korean search terms; two authors independently reviewed the 14 studies that met the selection criteria. Studies on the topic were concentrated in Australia and some European countries; most of them u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 43 publications
1
33
0
1
Order By: Relevance
“…Psychological nursing intervention focuses on taking targeted intervention measures according to the psychological state of patients. First of all, we need to accurately evaluate the psychological state of patients, formulate scientific and reasonable psychological intervention plans and measures according to the evaluation results, and carry out effective psychological counseling through communication [25][26][27]. Popularizing patients' disease knowledge, explaining in detail the harm of negative emotions to the disease, and pushing pictures and videos among patients provide convenience for patients to learn.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological nursing intervention focuses on taking targeted intervention measures according to the psychological state of patients. First of all, we need to accurately evaluate the psychological state of patients, formulate scientific and reasonable psychological intervention plans and measures according to the evaluation results, and carry out effective psychological counseling through communication [25][26][27]. Popularizing patients' disease knowledge, explaining in detail the harm of negative emotions to the disease, and pushing pictures and videos among patients provide convenience for patients to learn.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the sentiment of the "Compassion First" report developed by the National Suicide Prevention Taskforce as part of the Interim Advice to the Prime Minister: "Australia's approach to suicide prevention must be informed by the experiences and wisdom of people with lived experience of suicide and recovery" [58]. Furthermore, this finding is in line with the increasing involvement of people with lived experiences or "consumers" in the development and delivery of services [59] and education programs for health professionals [51,60]. A coproduction approach with people with lived experiences of suicidality creates richer learning outcomes for the student and the person/s and/or populations that they may be supporting [61,62].…”
Section: Discussionmentioning
confidence: 95%
“…While there has been an increase in mental health consumer involvement in health professions education (Arblaster et al, 2015a ; Classen et al, 2021 ; Happell et al, 2014 ; Kang & Joung, 2020 ), a recent review of occupational therapy programmes in Australia and Aotearoa New Zealand found that most programmes engaged consumers in teaching, but that this was generally at the level of “telling their story” and consumer involvement in co‐design of content was limited (Scanlan et al, 2020 ). This review identified numerous barriers to greater consumer involvement in education.…”
Section: Introductionmentioning
confidence: 99%